Pelatihan Pembuatan Eco-enzyme Berbasis Limbah Hortikultura Sebagai Pupuk Cair dalam Budidaya Aquaponik - Arista, Yuvita Lira (Universitas Aufa Royhan Di Kota Padangsidipuan, 2025)
Graha Indah Sub-district, RT 25, North Balikpapan, is one of the areas that has long implemented aquaponic cultivation. In aquaponic systems, plants require adequate nutrient input for optimal growth. Generally, fish waste produced in the system can serve as a natural fertilizer. However, excessive accumulation of fish waste can be harmful and toxic to the fish being cultivated. Therefore, an alternative source of nutrients is required to support plant growth, one of which is the use of eco-enzyme. Eco-enzyme can be produced through the fermentation of household organic waste such as (pineapple, guava, dragon fruit, banana, and orange) residues—combined with palm sugar and water in a ratio of 3:1:10. Eco-enzyme is highly suitable for application in aquaponic systems as it contains essential plant nutrients such as nitrogen (N), phosphorus (P), and potassium (K), which are crucial for plant development. In addition, eco-enzyme has the potential to convert ammonia—produced from fish waste into nitrate, which can be readily utilized by plants. The initiative of processing household organic waste into eco-enzyme in Graha Indah Sub-district, RT 25, presents a sustainable solution for organic waste management. The resulting eco-enzyme can be utilized as an organic input in aquaponic cultivation systems. The community service program (PkM) was deemed successful, as all participants achieved evaluation scores in accordance with the predetermined standards.